(untitled) (Research, Society and Development, 2022)
Objective: Validate a Standard Operating Procedure for the flow of care for acute Chagas disease in Pernambuco. Methodology: Methodological study, based on two stages proposed by Hoskins, concept analysis and content validity, with validation performed by five experts. To analyze the answers, the Percentage of Agreement between the judges was used, considering appropriate the items that obtained a percentage greater than or equal to 80%. Results: The final Percentage of Agreement among the judges in the evaluation instrument of the Standard Operating Procedure for the flow of care for acute Chagas disease in Pernambuco was 88%. Final considerations: The importance of the standard operating procedure in health care for individuals affected by acute Chagas disease was emphasized, thus enabling a safe practice, an improvement of care, and access to services, in addition to technical-scientific support for professionals in Primary Health Care.